Impact of Ocean Acidification on the Energy Metabolism and Antioxidant Responses of the Yesso Scallop (Patinopecten yessoensis) - Liao, Huan; Yang, Zujing; Dou, Zheng; Sun, Fanhua; Kou, Sihua; Zhang, Zhengrui; Huang, Xiaoting; Bao, Zhenmin (Frontiers in Physiology, 2019)
Ocean acidification (OA), which is caused by increasing levels of dissolved CO2 in the ocean, is a major threat to marine ecosystems. Multiple lines of scientific evidence show that marine bivalves, including scallops, are vulnerable to OA due to their poor capacities to regulate extracellular ions and acid-based status. However, the physiological mechanisms of scallops responding to OA are not well understood. In this study, we evaluated the effects of 45 days of exposure to OA (pH 7.5) on the energy metabolism and antioxidant capability of Yesso scallops. Some biochemical markers related to energy metabolism (e.g., content of glycogen and ATP, activity of ATPase, lactate dehydrogenase, glutamate oxaloacetate transaminase and glutamate-pyruvate transaminase), antioxidant capacity (e.g., reactive oxygen species level, activity of superoxide dismutase and catalase) and cellular damage (e.g., lipid peroxidation level) were measured. Our results demonstrate that the effects of the reduced pH (7.5) on scallops are varied in different tissues. The energy reserves are mainly accumulated in the adductor muscle and hepatopancreas. Yesso scallops exhibit energy modulation by increasing lactate dehydrogenase activities to stimulate anaerobic metabolism. The highly active Na+/K+-ATPase and massive ATP consumption in the mantle and gill indicate that a large amount of energy was allocated for the ion regulation process to maintain the acid-base balance in the reduced-pH environment. Moreover, the increase in the reactive oxygen species level and the superoxide dismutase and catalase activities in the gill and adductor muscle, indicate that oxidative stress was induced after long-term exposure to the reduced-pH environment. Our findings indicate that the effects of OA are tissue-specific, and physiological homeostasis could be modulated through different mechanisms for Yesso scallops.